Underwater Leidenfrost nanochemistry for creation of size-tailored zinc peroxide cancer nanotherapeutics - Mady Elbahri (Nature Portfolio, 2017)
Water can function as a sustainable reactor for the synthesis of size-controlled, functional nanoparticles. Here, the authors introduce an underwater Leidenfrost synthesis that reproduces the dynamic chemistry of the deep ocean, in which anticancer therapeutic ZnO2nanoclusters form in an overheated zone and migrate to colder water to continue growth.